Insulin Increases Sestrin 2 Content by Reducing Its Degradation through the PI3K/mTOR Signaling Pathway - Dandan Chai; Guoyu Wang; Ziyu Zhou; Hanyan Yang; Zhiwen Yu (International Journal of Endocrinology)
Sestrin (SESN) is known as a cysteine sulfinic acid reductase. Recently, nonredox functions of SESN in metabolic regulation and antitumor property have been recognized. While mechanisms underlying the expression of SESN are not fully understood. Here we report that insulin markedly increased SESN2 level in HepG2 cells through mTOR activation. To determine whether insulin affects SESN2 degradation, we assessed SESN2 turnover by applying the protein synthesis inhibitor, cycloheximide (CHX), and found that following insulin treatment SESN2 protein levels were reduced significantly slower than non-insulin-treated cells. Furthermore, the proteasomal inhibitor, MG132, dramatically increased SESN2 protein and its ubiquitination level while in the presence of MG132 insulin did not further increase SESN2 content, suggesting that insulin increases SESN2 content mainly via inhibiting its proteasomal degradation. We then explored the potential feedback role of SESN2 in insulin signaling by SESN2 siRNA knockdown in HepG2 cells. Following SESN2 knockdown insulin-stimulated PKB phosphorylation was enhanced and accompanied by reduced PTEN content. Taken together, our study suggests that insulin upregulates SESN2 content via the PI3K/mTOR signaling pathway and this effect is attributed to decreased SESN2 degradation. Furthermore, SESN2 via modulating PTEN plays a negative feedback role in insulin signaling.